Bringing art to life : a biography of Alan Jarvis - Horrall, Andrew (McGill-Queen's/Beaverbrook Canadian Foundation studies in art history, 2009)
In 1959, Alan Jarvis - the brilliant and charismatic director of the National Gallery of Canada - was forced to resign following a disagreement with the government over the purchase of works by European Old Masters. He never fully recovered from this dismissal, or the public humiliation that followed, succumbing to alcoholism in a little over a decade.